2012
DOI: 10.2298/ciceq111020064h
|View full text |Cite
|
Sign up to set email alerts
|

Structure evolution and mechanical behavior of poly(ethylene terephthalate) fibers drawn at different number of drawing stages

Abstract: In this work, the structure, mechanical and thermal properties of PET fiber obtained by hot multi-stage drawing have been investigated in terms of their dependence on the number of drawing steps at an equivalent total draw ratio. Differential scanning calorimetry, birefringence, wide-angle x-ray diffraction, FTIR spectroscopy, tensile properties, and taut-tie molecules were used to characterize the fine structure and physical properties of the fibers. Results have been explained in terms of a higher draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…PET filaments are known to have a higher stiffness in comparison to other polymer textile fibers [39, 40]. This is mainly due to its tendency to develop a conformation with stretched polymer chains together with the presence of aromatic rings in the polymer’s backbone [40, 41], as shown in figure 1. One of the main parameters affecting the compressive properties of polymer fibers is their ability to form lateral intermolecular interactions [7], which in most cases consist of secondary type of bonding.…”
Section: Resultsmentioning
confidence: 99%
“…PET filaments are known to have a higher stiffness in comparison to other polymer textile fibers [39, 40]. This is mainly due to its tendency to develop a conformation with stretched polymer chains together with the presence of aromatic rings in the polymer’s backbone [40, 41], as shown in figure 1. One of the main parameters affecting the compressive properties of polymer fibers is their ability to form lateral intermolecular interactions [7], which in most cases consist of secondary type of bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Further, results from crystallinity evaluation of annealed and thereby shrunk fibres are presented in Table 4 and show that crystallinity is unaffected also after shrinkage at 75 C, 90 C and 140 C. As mentioned earlier, previous studies made on PET fibres have showed that shrinkage is attributed to disorientation of non-crystalline regions. 33 This study has shown that the crystalline phase is unaffected from stretching and that shrinkage increase with degree of stretching, thus why we can say that stretching SrPET material in a heated state before compression moulding influence the non-crystalline regions in the HTPET fibres. The method to characterize shrinkage by DMA has been proven to work well for fibre as well as for laminates.…”
Section: Resultsmentioning
confidence: 82%
“…DSC is another common method that is used to describe morphology through information on first and second order transitions 24 and DMA is a method that provides information about structure and property relationships. 25,26 Substantial effort has been put into studying microstructure of PET both as film 2731 and fibre 3235 and these studies provide good information on how data shall be obtained and interpreted when applying these methods on SrPET.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral order index (LOI) can be related to several factors such as the crystallinity, reflection, size, and the distribution of the crystallites [21]. It reflects, the ordered regions perpendicular to the chain direction and was calculated from the following equation:…”
Section: Resultsmentioning
confidence: 99%
“…The crystal size (L) was determined from the half-height width of the crystalline reflections using the Scherrer Equation [21]:…”
Section: Characterizationmentioning
confidence: 99%